Exploiting physical vapor deposition for morphological control in semi‐crystalline polymer films. Issue 4 (12th October 2018) - Wang, Yucheng; Jeong, Hyuncheol; Chowdhury, Mithun; Arnold, Craig B.; Priestley, Rodney D.
Abstract : Research in semi‐crystalline polymer thin films has seen significant growth due to their fascinating thermal, mechanical, and electronic properties. In all applications, acquiring precise control over the film morphology atop various substrates or in the free‐standing film geometry is key to advancing product performance. This article reviews the crystallization of polymer thin films processed via physical vapor deposition (PVD). Classical PVD techniques are briefly reviewed, highlighting their working principles as well as successes and challenges to achieving morphological control of polymer films. Subsequently, the recent development of a unique PVD technique termed Matrix Assisted Pulsed Laser Evaporation (MAPLE) is highlighted. The non‐destructive technology overcomes the major drawback of polymer degradation by classical PVD. Recent advances highlighting how MAPLE can be exploited to control polymer film morphology in ways not achievable by other methods are presented. Challenges and future scope of PVD for polymer film deposition concludes the review. Abstract : This article highlights the morphology and properties of semi‐crystalline polymer films formed via physical vapor deposition (PVD), with a particular emphasis on Matrix Assisted Pulsed Laser Evaporation (MAPLE), an emerging deposition technology, for the gentle deposition of polymers. The article focuses on elucidating general processing‐structure‐property relationships of polymer films formed by several PVD approaches. Such studies are of tremendous importance, as polymer thin films enable applications ranging from solar cells to sensors.